2014
DOI: 10.3892/ol.2014.2284
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic invasion of micropapillary cancer cells is associated with a poor prognosis of pathological stage IA lung adenocarcinomas

Abstract: The cancer cells of lung adenocarcinoma with a micropapillary pattern (MPP) have been found to frequently invade lymphatic vessels, and the prognosis of patients with lung adenocarcinoma with an MPP is poor. In the present study, the cancer cells of lung adenocarcinomas containing an MPP were found to express vimentin more extensively than those in lung adenocarcinoma without an MPP. The contribution of cancer cells in the MPP component to adenocarcinoma lymphatic invasion was assessed using vimentin as a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…In the present study, we clearly demonstrated that vimentin expression was very prevalent in MPC and was detected in 95/101 (94.1%) AC‐MPC, in accordance with the results of the recent study of Hirano et al . Furthermore, the expression levels were also markedly up‐regulated in MPC, and the vimentin scores of MPC were significantly higher than those of the well‐ and moderately differentiated CAC, as well as the background non‐MPC of the AC‐MPC.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, we clearly demonstrated that vimentin expression was very prevalent in MPC and was detected in 95/101 (94.1%) AC‐MPC, in accordance with the results of the recent study of Hirano et al . Furthermore, the expression levels were also markedly up‐regulated in MPC, and the vimentin scores of MPC were significantly higher than those of the well‐ and moderately differentiated CAC, as well as the background non‐MPC of the AC‐MPC.…”
Section: Discussionsupporting
confidence: 92%
“…first suggested the prognostic significance of MPC in lung cancers, especially the risk of highly frequent metastasis, because 33 of their 35 AC‐MPC developed metastases . Most, if not all, subsequent studies have shown that MPC was an adverse prognostic indicator in lung cancers . In the present study, the OS and DFS of AC‐MPC were also significantly worse than those of CAC.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations